2015
DOI: 10.1136/bmjsem-2015-000065
|View full text |Cite
|
Sign up to set email alerts
|

Eucapnic voluntary hyperpnoea and exercise-induced vocal cord dysfunction

Abstract: IntroductionExercise-induced bronchoconstriction (EIB) is a common condition in endurance athletes. Exercise-induced vocal cord dysfunction (EIVCD) is a frequent confounder of EIB. The diagnosis of EIVCD may be challenging and can be missed as the problem is often intermittent and may only occur during intense exercise. Eucapnic voluntary hyperventilation (EVH) is the best test to detect EIB. This pilot study aimed to assess if EVH could be helpful in the diagnosis of EIVCD associated or not to EIB in athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In a retrospective chart review of university athletes presenting with exertional respiratory complaints, postexertional laryngoscopy (among other tests) identified EILO in 70% of athletes, and 37% had coexisting asthma 30. In a cross-sectional study of 352 athletes who underwent EVH challenge during flexible laryngoscopy, 41 (12%) were suspected of having EILO 31. EILO was verified in all 41 athletes, using a surrogate challenge that did not reproduce respiratory distress 31.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective chart review of university athletes presenting with exertional respiratory complaints, postexertional laryngoscopy (among other tests) identified EILO in 70% of athletes, and 37% had coexisting asthma 30. In a cross-sectional study of 352 athletes who underwent EVH challenge during flexible laryngoscopy, 41 (12%) were suspected of having EILO 31. EILO was verified in all 41 athletes, using a surrogate challenge that did not reproduce respiratory distress 31.…”
Section: Observationsmentioning
confidence: 99%
“…In a cross-sectional study of 352 athletes who underwent EVH challenge during flexible laryngoscopy, 41 (12%) were suspected of having EILO 31. EILO was verified in all 41 athletes, using a surrogate challenge that did not reproduce respiratory distress 31. In 37 healthy rowers without respiratory complaints, EIB was diagnosed in 27% and EILO was diagnosed in 43%.…”
Section: Observationsmentioning
confidence: 99%
“…Supposedly, there were similarities between persons displaying exercise-induced VCD and persons experiencing exercise-induced laryngomalacia [62]. More extensive research suggested that exercise-induced inspiratory stridor could be an alternative movement of the supraglottic structures unresponsive to prescribed medications [57,[63][64][65]. Under the latter situation, VCD might just be a physiologic alteration where breathing restriction begins in a supraglottic structures and VCD happens as a secondary phenomenon [13].…”
Section: Discussionmentioning
confidence: 99%
“…Under the latter situation, VCD might just be a physiologic alteration where breathing restriction begins in a supraglottic structures and VCD happens as a secondary phenomenon [13]. In fact, Turmel et al utilized eucapneic voluntary hyperventilation to uncover cases of VCD and recommended dividing exercise-induced VCD into three categories: supraglottic, glottic and mixed (glottic and supraglottic) obstruction [63]. But besides VCD itself, there are other physiologic changes associated with intense exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Elite or intense-training athletes as well as swimmers, runners and cold-air athletes are at the greatest risk for VCD development [206,207,242]. Eucapneic voluntary hyperventilation testing can uncover some cases of VCD divided into three categories of supraglottic, glottic and mixed (glottic and supraglottic) upper airway obstruction [243].…”
Section: Featurementioning
confidence: 99%